อำนาจในการฟ้องคดีของคณะกรรมการป้องกันและปราบปรามการทุจริตแห่งชาติ (ป.ป.ช.) ตามมาตรา 272 แห่งรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 - ณัฐวุฒิ รัตนนาคินทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This thesis is to study, analyze and compare with the prosecution power of the Person Holding Political Positions to the national anti-corruption commission (NACC) and the Attorney General. As a constitution, it specifies that both organizations can sue as the inspection of the exercise of State power to give the maximum benefit for the protection of the civil right and liberty. However, the problem that such a regulation authorizing NACC to prosecute their own, it is appropriate or not. It is therefore important to study how such organization. To understand the correct and appropriate guidelines on the existing organization, it should be studied and compared different samples with the development, validation and use of state power.The results showed that the State actions must be done through the natural person who is a state representative. This could be done in addition to boundary, conditions or rules, as defined by law, with bad faith or other external factors that are illegal for the purposes of the benefits to their cronies. In Thailand, the prosecution of Attorney General and the NACC will always check and balance each other as Organic Act on Criminal Procedure for Persons Holding Political Positions B.E. 2542, section 10 is based on the principle of Constitutionalism ideas. Moreover, in the court proceeding, no matter whether the Attorney General or NACC is the plaintiff itself, the organization must be reviewed by the courts as well. Therefore, in the case that reports or documents are not completed, Court may order dismissal to give the maximum benefit to the people.